2019
DOI: 10.1021/acs.nanolett.9b02853
|View full text |Cite
|
Sign up to set email alerts
|

Global Alignment of Solution-Based Single-Wall Carbon Nanotube Films via Machine-Vision Controlled Filtration

Abstract: Over the past decade, substantial progress has been made in the chemical processing (chiral enrichment, length sorting, handedness selectivity, and filling substance) of single-wall carbon nanotubes (SWCNTs). Recently, it was shown that large, horizontally-aligned films can be created out of post-processed SWCNT solutions. Here, we use machine-vision automation and parallelization to simultaneously produce globally-aligned SWCNT films using pressure-driven filtration. Feedback control enables filtration to occ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 72 publications
0
50
0
Order By: Relevance
“…concluded that the grooves are not the most important aspect for alignment but rather a directional charging of the surface, which can be further enhanced by tribo‐charging the membrane. [ 46 ] Nevertheless, it is commonly agreed upon that alignment occurs near to, but not directly on the membrane surface. [ 27,39,43,44,46 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…concluded that the grooves are not the most important aspect for alignment but rather a directional charging of the surface, which can be further enhanced by tribo‐charging the membrane. [ 46 ] Nevertheless, it is commonly agreed upon that alignment occurs near to, but not directly on the membrane surface. [ 27,39,43,44,46 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 46 ] Nevertheless, it is commonly agreed upon that alignment occurs near to, but not directly on the membrane surface. [ 27,39,43,44,46 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 ] Most recently, Walker et al induced machine vision‐driven feedback and surface treatment of the glassware into the process. [ 19 ]…”
Section: Emergent Electrical Properties Of Nanotube Assembliesmentioning
confidence: 99%
“…CNT film, a macroscopic assembly of nanoscale individual CNTs, can be fabricated by various approaches, such as floating catalyst chemical vapor deposition (FCCVD) [ 16 , 17 , 18 ], dry spinning [ 19 ], solution-based coating [ 20 ], printing [ 21 ] and vacuum filtration [ 22 ], with different types of architectures, including non-woven cloth, vertical alignment, aligned networks, transparent film, random planar film and compressible foams [ 23 ].…”
Section: Introductionmentioning
confidence: 99%